Therapeutic Management of Notoedric Mange in Rabbits - Patel, Bhavika R; Chauhan, Vandip D; Prajapati, Ankit S; Joseph, Joice P; Vasava, Amrita A (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Mange in rabbits is a highly contagious and a rising disease  caused by different burrowing and non-burrowing  mite species protozoon. Rabbits occasionally get infestated  with Notoedres cati, which burrow the superficial layers of  skin (Darzi et al., 2007). The mange infestation is widespread  throughout the different parts of the world, with lesions first  appearing on the lips and nose before spreading to the rest  of the face. However, additionally crucial to zoonotic research,  burrowing mites can cause humans to get dermatitis that  is temporarily itchy. This mange spreads speedily through  direct contact with skin or interaction with the environment  (Panigrahi et al., 2016), and it can infect an immense number  within a short duration of time. Only the adult female will  pierce the skin and create a tunnel to deposit eggs. Adult male  and older larvae stay on the skin surface. It takes two or three  weeks to complete the life cycle from eggs to adulthood. If  proper management practices are not implemented, this  mange can cause severe pruritis and self-inflicted scratches  that can result in secondary pyoderma, and it poses a serious  threat to rabbit colonies. It is challenging to apply topical  medication to eradicate a mite infestation, but ivermectin  is simple to use and effective at clearing the skin of mange  (McKellar et al., 1992). The present clinical case report explains  Notoedric mange in two rabbits and its successful therapeutic  management with the use of Ivermectin subcutaneously.
Keywords: protozoon; Notoderes; burrowing